Physical activity and health indicators in people living with HIV/aids - Cordeiro, Hygor; Kitagawa, Lidyane Midori; Máximo, Milena Arantes; Dias, Douglas Fernando; Guariglia, Débora Alves (ABCS Health Sciences, 2018)
Introduction: An active lifestyle may contribute significantly to people living with HIV/aids by improving physical abilities and reducing the adverse effects of medications. Objective: To analyze the association between physical activity and sociodemographic and health factors in people living with HIV/aids in the municipality of Ourinhos-SP. Methods: Patients undergoing treatment were interviewed at the Specialized Infectious Diseases Care Service. Habitual physical activity and its domains were evaluated using the Baecke questionnaire and patients’ charts were consulted for additional health data. Results: The proportion of individuals undertaking leisure physical activity in our sample was low (21%). Poisson regression models, adjusted for confounding factors, identified associations between occupational physical activity and higher social class (PR: 3.32; 95% CI: 1.34-8.25); between leisure physical activity and locomotion and higher diastolic blood pressure (DBP) (PR: 3.17; 95% CI: 1.43-7.07); and between habitual physical activity and duration of diagnosis >150 months (PR: 3.18; 95% CI: 1.16-8.72) and higher prevalence of leisure physical activities was associated with higher social class (PR: 2.86, 95% CI: 1.11-7.36). Conclusion: People living with HIV/aids and undergoing treatment in the Ourinhos region have low levels of physical activity. Furthermore, social class, duration of diagnosis and DBP were found to be associated with physical activity.